Effect of Subtitles on Gaze Behavior during Shot Changes: An Eye-tracking Study - Prakash Padakannaya; Jeril Joy (International Journal of Psychological Research, 2023)
The study provides a comprehensive picture of the effect of subtitles on the gaze behavior of the participants while watching continuity editing and discontinuity editing style cinema. Three video clips (with English subtitles and without subtitles) of continuity editing and discontinuity editing styles were presented to participants. The video clips came from English movies and the participants were not native English speakers. Entry time, dwell time, first fixation time, scan path, and average fixation duration were taken as dependent variables in this within-group study. The eye-tracking data gathered were subjected to repeated measures of two-way ANOVA and paired t-test. Results revealed that the appearance of subtitles at the bottom of the screen changed the eye movement pattern of the participants during the shot changes. Timing of the subtitle starting point (before the cut or after the cut) also affected the gaze behavior. The editing style, however, did not make any difference in the gaze behavior of participants while watching subtitled video clips. Further, participants preferred reading subtitles to seeing visual images even if the subtitles were presented during the shot changes.